Rifting and magmatism in the northeastern South China Sea from wide‐angle tomography and seismic reflection imaging. Issue 3 (5th March 2014) - Lester, Ryan; Van Avendonk, Harm J. A.; McIntosh, Kirk; Lavier, Luc; Liu, C.‐S.; Wang, T. K.; Wu, F.
Abstract We present a new travel time tomography velocity model and seismic reflection images that delineate the rift architecture and magmatic features of the rifted margin in the northeastern South China Sea. These data reveal moderately stretched crust ~25 km thick along the continental shelf and thin but laterally variable crustal thickness in the distal margin. Along the continental slope, crust rapidly thins to ~4 km in a basin characterized by tilted fault blocks that sole into a low‐angle detachment. Strain was localized to a degree within the highly stretched basin but failed to progress to breakup and seafloor spreading. Crust in the distal margin is ~12–15 km thick. Few extensional structures are apparent in the distal margin, but seismic velocities are suggestive of highly thinned and magmatically intruded continental crust. The magmatic features we interpret include volcanic zones at the top of the basement that deform or disrupt overlying postrift strata, sills intruded into the postrift sedimentary section, and a high‐velocity (~6.9–7.5 km/s) lower crustal layer that we take to be magmatic underplating or pervasive lower crustal intrusions. These features primarily occur in the distal margin and may have been emplaced during postrift seafloor spreading. The postrift magmatism may have been induced by convective removal of continental lithosphere following breakup and the onset of seafloor spreading in the South China Sea.